Mechanical Properties of Coconut Fibers Reinforced Polyester Composites - Mulinari, D. R.; Baptista, C. A. R. P.; Souza, J. V. C.; Voorwald, H. J. C. [UNESP]; Guagliano, M.; Vergani, L. (Elsevier B.V., 2011)
Actually, studies about the utilization of natural fibers as reinforcement in polymeric composites are increasing due to the improvements that fibers can provide to the product. In this work, chemical modification of the coconut fibers by alkaline treatment was studied in order to use them as reinforcement in polyester resin. Coconut fibers were modified during 1 hour with sodium hydroxide solution 1% wt/v. The modified fibers were evaluated by scanning electron microscopy, X-ray diffractometry, thermal analysis and Fourier Transform infrared spectroscopy. The composites were prepared by compression molding technique using 10% wt of fibers. The mechanical properties were evaluated by tensile and fatigue tests. The surfaces of the fractured specimens were examined in order to assess the fracture mechanisms. Results presented a decrease in fatigue life of composites when applied greater tension, due to bonding interfacial, which was not adequate. (C) 2010 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of ICM11
Keywords: Coconut fibers; Composites; Fatigue; Interfacial bonding